Penerapan Manajemen Risiko pada Tingkat Efisiensi Keuangan di Bank DKI Jakarta - Saridawati Saridawati; Murniyati Murniyati; Ratih Hastasari; Suharini Suharini (Politeknik Ganesha Medan, 2021)
Efficiency is one measure of bank performance. The efficiency of a bank is influenced by the way management manages risk. Financial services authority regulation number 18 /pojk.03/2016 issued by Bank Indonesia which requires every bank in Indonesia to form a risk management team. Risk management problems in the banking world are related to the losses they experience, and Regional Development Banks are expected to be able to detect maximum losses that may arise in the future. This team is obliged to control various aspects of risk management in each bank and observe the impact of risk management implementation. This study aims to determine the efficiency level of conventional banking at PT Bank Pembangunan Daerah Jawa Tengah and the effect of financing risk, operational risk and liquidity risk on the efficiency level. Efficiency is measured by the method of Operating Expenses from Operating Income. The data used as the object of this research is Bank DKI Jakarta for the 2015-2020 period. The level of influence of the variables X1, X2, X3 on Y on the determinant coefficient (R2) shows the Adjusted R Square number of 0.359 or 35.9% which means that the variation in efficiency level can be explained by financing risk, operational risk and liquidity risk, the remaining 64.1% can be explained from other variables outside, for previous related studies there is no similarity in the influence of independent (x) and dependent (Y) values, because of differences in values ??generated from SPSS processing data. Based on the results of statistical tests and discussion analysis, it is known that financing risk, operational risk, liquidity risk simultaneously have no effect on the level of efficiency and only financing risk has a significant positive effect on the level of efficiency at PT Bank DKI Jakarta.